(untitled) (Biological Sciences - PJSIR, 2016)
Lipases are important hydrolytic enzymes that hydrolyze long chain triacylglycerol into diacylglycerol, monoacylglycerol, glycerol and fatty acids. Lipases are found in microorganisms, fungi, plants and animals. Commercially, useful extracellular lipases are isolated from different bacterial species, including Bacillus, Achromobacter, Alcaligenes, Arthrobacter, Pseudomonas, Staphylococcus and Chromobacterium species. Among the Pseudomonas species, Pseudomonas aeruginosa, P. cepacia and P. fluorescence are the major producers of lipases. Bacterial lipases have great industrial applications because of their stability, selectivity and broad substrate specificity. Due to their large scale application in industrial sectors, attention is given to isolate Pseudomonas lipases. In this review, purification strategies for lipases isolated from Pseudomonas species have been focussed.